PENGEMBANGAN MODUL AJAR BERBSIS BUDAYA NYIRU JAJE BEJANGKONGAN UNTUK MENINGKATKAN KARAKTER ANAK KELOMPOK B DI TK ISLAM AL-QUDSIYAH PRINGGASELA - Lestari, Widia; Nurhasanah; Baiq Nada Buahana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a feasible and effective teaching module based on the Nyiru Jaje Bejangkongan culture. The research uses a Research and Development (R&D) method with the 4D development model, which includes the stages of define, design, develop, and disseminate. The study subjects are 30 children in Group B at TK Islam Al-Qudsiyah Pringgasela. Data collection techniques were carried out through observation, interviews, questionnaires, and documentation. The data were analyzed descriptively and quantitatively to determine the feasibility and effectiveness of the developed module. Research results show that the teaching module based on Nyiru Jaje Bejangkongan culture is very feasible, with a media expert rating of 94% and a material expert rating of 90%. The effectiveness of the teaching module implemented in group B shows that the N-Gain calculation results in a value of 0.3, indicating that the developed teaching module falls into the moderate category. Thus, the Nyiru Jaje Bejangkongan culture-based teaching module is effective and feasible to use in the learning process and can improve children's character, especially in aspects of cooperation, sharing, gratitude, and social care through contextual, enjoyable, and local culture-based learning.